Development of novel Ti-Mo-Mn alloys for biomedical applications - Lourenço, Mariana Luna [UNESP]; Cardoso, Giovana Collombaro [UNESP]; Sousa, Karolyne dos Santos Jorge [UNESP]; Donato, Tatiani Ayako Goto [UNESP]; Pontes, Fenelon Martinho Lima [UNESP]; Grandini, Carlos Roberto [UNESP] (Springer Nature, 2020)
Due to excellent biocompatibility and corrosion resistance, the application of titanium alloys in orthopedic and dental implants has been increasing since the 1970s. However, the elasticity of these alloys as measured by their Young’s modulus is still about two to four times higher than that of human cortical bone. The most widely used titanium alloy for biomedical applications is Ti-6Al-4V, however, previous studies have shown that the vanadium used in this alloy causes allergic reactions in human tissue and aluminum, also used in the alloy, has been associated with neurological disorders. To solve this problem, new titanium alloys without the presence of these elements and with the addition of different elements, usually beta-stabilizers, are being developed. Manganese is a strong candidate as an alloying element for the development of new beta-type titanium alloys, due to its abundance and low cytotoxicity. In this study, Ti-10Mo-5Mn, Ti-15Mo-2.5Mn and Ti-15Mo-5Mn alloys were prepared in an arc furnace, which resulted in an alloy structure clearly showing the predominance of the beta phase with a body-centered cubic crystalline structure. The observed microstructure confirmed the results on the structural characterization of alloys. Measurement of the indirect cytotoxicity of the alloys showed that the extracts of the studied alloys are not cytotoxic for fibroblastic cells.